The Portuguese justice in the Middle Ages (An inventory of doubts) - Duarte, Luis Miguel (Cuadernos de Historia del Derecho, 2005)
This paper tries to raise some of the main questions about the way of the portuguese judicial system worked in the Late Middle Ages. The first one concerns the effectiveness of the laws (specially the Ordenações Afonsinas). Then we examine the lay landlord’s justice, the conflicts and cooperation between that and the king’s justice, the ecclesiastical justice, trying again to establish the part of the oppositions and the part of complementarities, to end with the local justice and in particular the local judges their profile, their cultural and juridical preparation. A last question regards the relations between those different judicial systems and the non linear evolution of the whole judicial world.